TELAAH KRITIS TERHADAP PENERAPAN HUKUM PIDANA PENCUCIAN UANG YANG BERASAL DARI KEJAHATAN PENIPUAN - Nurohim, Hamdan (The Juris, 2025)
This study examines the application of criminal law to the offence of money laundering derived from fraudulent activities, using the Supreme Court Decision Number 77 K/Pid.Sus/2018 as a case study. Within the Indonesian legal system, money laundering is regulated under Law Number 8 of 2010 and classified as an offence outside the Penal Code (KUHP). The research adopts a normative juridical approach with a descriptive qualitative method to analyse both the normative provisions and judicial implementation relevant to the case. The findings indicate that money laundering constitutes a follow-up crime, requiring a predicate offence—such as fraud—as its basis. In the examined decision, the Supreme Court held that although the elements of fraud were not legally proven at the first and appellate court levels, the defendant’s actions fulfilled the elements under Article 5 of the Anti-Money Laundering Law, thus leading to the cassation being granted and a sentence imposed. The judgment reflects a proportional application of juridical, sociological, and philosophical principles by the judges. Furthermore, the study highlights the increasing complexity of modern banking systems and technology in facilitating money laundering practices. Consequently, a more integrative and adaptive law enforcement strategy is required to address the evolving dynamics of financial crime.